RUNX1 Mutations in Inherited and Sporadic Leukemia - Bellissimo, Dana C.; Speck, Nancy A. (Frontiers in Cell and Developmental Biology, 2017)
RUNX1 is a recurrently mutated gene in sporadic myelodysplastic syndrome and leukemia. Inherited mutations in RUNX1 cause familial platelet disorder with predisposition to acute myeloid leukemia (FPD/AML). In sporadic AML, mutations in RUNX1 are usually secondary events, whereas in FPD/AML they are initiating events. Here we will describe mutations in RUNX1 in sporadic AML and in FPD/AML, discuss the mechanisms by which inherited mutations in RUNX1 could elevate the risk of AML in FPD/AML individuals, and speculate on why mutations in RUNX1 are rarely, if ever, the first event in sporadic AML.